(R)evolution of performance in the public order and safety system - Elena Casandra Ceausescu; Camelia Cazoni; Bogdan Petre; Alexandra Pircalaboiu; Marian Nastase (Journal of Research and Innovation for Sustainable Society)
The public order and safety system in Romania has several valences of national importance for which the internal management control mechanisms must be adapted to the general and specific objectives of the entity, so that the institutional needs related to the safety of the citizen and the preservation of a climate of public tranquility are realized at an optimal and continuous level. In this respect, at the managerial level it is analyzed through information, communication and management of certain documents, how to achieve general and specific objectives through planning tools, the degree of achievement of targets, the, performance monitoring, using the resources at hand. Case study was used as qualitative research in order to emphasize the particularities and evolution of performance evaluation in the public order and safety system. Thus, we can talk about the effectiveness of performance that is examined and evaluated in order to provide reasonable assurance that all the objectives of the public entity will be achieved. This study attempts to establish the evolution of performance indicators in the system of public order and safety, from the perspective of legislative changes in the field and the opinion of the authors based on the method of observation on the revolution of the system to the advantage or detriment of the entity. Also, a case study will indicate the results obtained and their evolution reported to the performance indicators at the level of the preventive arrest structure in Bucharest for the period 2019-2023.